Unveiling Future Trends in Employer Branding: Systematic Review and Bibliometric Analysis - SHIMMY FRANCIS; SANGEETHA R (International Journal of Information Science and Management)
Employer branding, an emerging area in Human Resource Management (HRM), has gained significant importance. Despite its importance, the literature on employer branding remains fragmented due to the absence of a comprehensive review that consolidates the intellectual structure of the field. This study addresses the existing knowledge gap by conducting a systematic literature review accompanied by bibliometric analysis utilizing performance analysis and science mapping through the Tableau software package. Through a comprehensive review of 27 articles, this study reveals the key branding elements, top journals, contributing countries, industries, citation trends, sample statistics, theoretical contribution, and six key themes (i.e., Employer branding attributes, sustainable employer branding, employee-centric employer branding, social media employer branding, recruitment strategies, HRM practices of employer branding) that characterize the body of the employer branding. Finally, the study has identified an integrative framework and set the direction for future research. It offers actionable recommendations for HR practitioners, emphasizing technology integration in employer branding initiatives and incorporating sustainable practices to enhance organizational attractiveness. This research contributes to a deeper understanding of the concept of employer branding. It provides valuable guidance for organizations seeking to navigate and optimize their employer branding strategies for the future.